2003
DOI: 10.1071/he03061
|View full text |Cite
|
Sign up to set email alerts
|

A population perspective of osteoporosis. How common? What impact? How modifiable?

Abstract: Issue addressed To determine the prevalence of diagnosed osteoporosis, to explore the level of perceived risk of people without the disease, to investigate qualitatively the reasons for the levels of perceived risk, the knowledge of what osteoporosis is and what effects the disease has on quality of life and well‐being. Methods Cross‐sectional household survey undertaken in metropolitan and country South Australia (SA) in 1998 with 3,001 randomly selected adults (18 years and over) interviewed. Respondents fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…This is an encouraging finding because females are at an increased risk to develop osteoporosis in later life if calcium intake is compromised during adolescence and young adulthood. Meanwhile, males switched their milk choices from low fat milk to fat free milk since their total milk consumption did not change, which may demonstrate males may not recognize osteoporosis as an immediate danger due to a broad notion that osteoporosis an "old woman's disease" [ 28 ]. It may be that the males chose fat free milk over low fat milk in an attempt to reduce fat intake, which was an important educational component in the classroom lectures and projects.…”
Section: Discussionmentioning
confidence: 99%
“…This is an encouraging finding because females are at an increased risk to develop osteoporosis in later life if calcium intake is compromised during adolescence and young adulthood. Meanwhile, males switched their milk choices from low fat milk to fat free milk since their total milk consumption did not change, which may demonstrate males may not recognize osteoporosis as an immediate danger due to a broad notion that osteoporosis an "old woman's disease" [ 28 ]. It may be that the males chose fat free milk over low fat milk in an attempt to reduce fat intake, which was an important educational component in the classroom lectures and projects.…”
Section: Discussionmentioning
confidence: 99%
“…Effective public health messages that provide clear recommendations and develop osteoporosis-related knowledge are vital in supporting efforts in osteoporosis prevention. Although the modification of lifestyle behaviours may contribute significantly to reducing the risk of this disease, Australian communities have been reported in a number of studies as having a lack of knowledge about osteoporosis [ 4 - 7 ], and thus a limited ability to competently reduce their risk of this disease by modifying their lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…One reason could be a lack of knowledge about the condition, as suggested by the study cited in our introduction (Taylor et al, 2003). A case in point was one participant in the community case study who had never experienced a fracture and reported having no knowledge of osteoporosis.…”
Section: Discussionmentioning
confidence: 95%
“…However, the statistics indicate that these measures are not universally effective. For example, a large Australian population survey reported that men and women across all age groups not only underestimated the risk of getting osteoporosis in the future but also had little knowledge of the disease and its risk factors (Taylor et al, 2003). This study of 3,001 randomly selected adults found that the overall perceived risk of getting osteoporosis was low (59.7%) or moderate (40.6%).…”
mentioning
confidence: 92%
See 1 more Smart Citation